Kommunikációs szektor az Északnyugat–Dunántúl térségében - Nagy, Gábor (Tér és Társadalom, 1997)
The location and the geographical situation of Nortwest Transdanubia require the rapid development of the telecommunication channels. In the rapidly growing business connections, during the building out of sub-contracting systems and supplier networks, a precondition of the success of local economies is keeping in continuous touch with the partners and the creation of new market cooperations. The strong external connections of the counties of Nortwest Transdanubia (intra- and interregional connections as well as connections reaching beyond the State border), the export-oriented economic structure, the number of joint ventures and the economic power that they represent all suggest that Western European level communication be created for the business sphere in the Nortwest Transdanubian counties. Furthermore, as several novelties arrive at Hungary through the strong external Iinks of the Nortwest Transdanubian region, the mediation of these innovations to the farther parts of Hungary requires high quality connection possibilities, with the help of which the region can fulfil its role, coming from its geographical position, as a bridge between Western Europe and Hungary. However, we should look further than this point. The favourable preconditions of the region provide an opportunity for the establishment of the basis of an information- and communication-oriented economic base. We have to see that the advantages from which the region’s present profits derive (high personal incomes, low unemployment) are not eternal but rather temporary endowments. The relatively skilled labour force, the relative proximity in space to the West and East European markets and partners and the relatively low wages only offer a short term opportunity lasting for not more than one decade or two, alleviating the process of restructuring. A fundamental issue of the communication-oriented development is the rapid transmission of the precise information to the appropriate customer. The channels for this can only be found in fragments at the moment. The Chambers as the most important conveyors of business information will have a huge role in this respect. The Business Centres have a similar role, also, the transition of the role of the traditional sources of information is expected (e.g. Statistical Agencies, Regional Information Service on the State Budget and Public Administration, Labour Offices). A pressure of opposite direction, i.e. influencing the national concepts with bottom-up strategic suggestions is also possible. In the distribution of the resources, the information sector should be given a weight bigger than until now. Setting the region on an information-oriented development track can be stated as an objective for the decisionmakers.